Jacques Lacan’s “Kant with Sade”: renunciation to desire and sadism in the Kantian categorical imperative - Conde Soto, Francisco (Anales del Seminario de Historia de la Filosofía, 2017)
The aim of this study is to evaluate the juxtaposition of Kant’s categorical imperative with Sade’s maxim exposed in several texts of the French psychoanalyst Jacques Lacan. According to Lacan Kant and Sade are two sides of the same coin in reference to their position with respect to desire and enjoyment. His thesis are: 1. Sade’s maxim that the libertine is entitled to vex his neighbor as he pleases essentially meets the requirements of Kant’s categorical imperative. 2. Both Sade and Kant’s theories are examples of only one sadism directed at other subjects the first and directed toward himself in the form of moral duty the second. Reading The Ethics of Psychoanalysis (1959-60) and especially the text “Kant with Sade” (1966) is exposed Lacan’s critique of the categorical imperative of Kant, taken as a paradigm of what it means to be moral.